Gender, Genre and the Globe: The Emergence of British Women’s Writing on India in the Long Eighteenth Century - Meena, Vaibhav; Kalra, Aditi (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The paper examines the emergence of British women’s writing on India during the long eighteenth century and explores how gender, genre, and global imperial expansion shaped their literary production. The period witnessed the gradual participation of women writers in travel writing, memoirs, letters, and fictional narratives. Despite facing social and institutional restrictions that limited women’s access to formal literary and intellectual spaces, several British women authors produced texts that documented their experiences, observations, and interpretations of Indian society, culture, and colonial life. These writings not only contributed to the growing body of colonial knowledge about India but also reflected the complex negotiations of gendered authority within imperial discourse. By situating these works within the historical context of the long eighteenth century, this paper traces the conditions that enabled women’s authorship while also highlighting the constraints imposed by patriarchal norms and publishing practices. It further analyses how women writers employed particular genres—especially travel narratives, epistolary accounts, and domestic memoirs—to articulate perspectives that differed from male colonial narratives. Ultimately, the paper argues that British women’s writing on India played a significant role in shaping early transnational literary exchanges and offers valuable insight into the intersections of gender, empire, and literary form in the eighteenth-century global context.